Aspects of later prehistoric settlement in Lincolnshire: a study of the Western Fen margin and Bain Valley - Chowne, Peter (1988)
The objective of this research was to examine the development of settlement in Lincolnshire during the 4th-1st millennia B.C. by a detailed investigation of two contrasting areas, the western fen margin and the Bain Valley.